Development of Agro-Edutourism Based on Sustainable Agroindustry in Ngestiharjo Village, Kulon Progo - Mulyati, Guntarti Tatik; Khuriyati , Nafis; Ainuri, Makhmudun; Ushada, Mirwan; Wagiman, Wagiman; Saroyo, Pujo; Pradita, Sintia Putri; Falah, Muhammad Affan Fajar; Widodo, Kuncoro Harto (JAKADIMAS (Jurnal Karya Pengabdian Masyarakat), 2024)
Lestari Mulya (LM) Agro-Edutourism is one of the Agro-Edutourisms included in the Aerotropolis Area, which is a tourist area supporting Yogyakarta International Airport (YIA) in Kulon Progo Regency. This Agro-Edutourism is a tourist destination designed for educational purposes for children who have received early childhood education and kindergarten students. The community services aim to support members of the Lestari Mulya Women Farmer Group as managers of the Agro-Edutourism to discover their potential, identify development alternatives and assist them to become a sustainable agroindustry. Rapid Rural Appraisal (RRA), Participatory Rural Appraisal (PRA), and Focus Group Discussion (FGD) methods were used by the Universitas Gadjah Mada community services team to gather the information needed for further development planning. The results of the in-depth interviews showed that there is potential for the land and that some ideas can be developed to improve the quality of Agro-Edutourism products. The Lestari Mulya Women Farmers Group was able to use the FGD method to design a safer and more comfortable layout for the area. The community services team has developed a master plan proposal to apply for funding to improve infrastructure to support faster development of the Agro-Edutourism